Validation and cultural adaptation of the Integrated Palliative care Outcome Scale (IPOS) for the Portuguese population - Antunes, Bárbara (2020)
Background: To culturally adapt and validate the Integrated Palliative care Outcome Scale to European Portuguese. Methods: Multi-centred observational study with 2 assessment points. Data were collected in nine centres using consecutive sampling. All patients were screened for eligibility. Inclusion criteria: ≥18 years, mentally fit to give consent, diagnosed with an incurable, potentially life-threatening illness, read, write and understand Portuguese. Translation and back translation with independent native speakers blind to the original measure created a Portuguese version, which was culturally adapted using cognitive interviews. For psychometric testing, the COSMIN checklist was followed. Reliability and content validity were assessed for patient and staff versions. Construct and criterion validity were tested for patient version. Results: 1703 individuals were screened between July 1st 2015 and February 2016, 135 (7.9%) were included. Mean age was 66.8 years (SD 12.7), 58 (43%) were female. Most patients (109; 80.7%) had a cancer diagnosis. Cronbach’s alpha showed good internal consistency, 0.657 for patient, 0.705 for staff versions. Intraclass correlation coefficient testing reproducibility revealed very good reliability, 0.794–0.950 for patient and 0.456–0.925 for staff versions. There was good content validity and significant results for construct validity. Physical symptoms were better detected by females. IPOS could discriminate: practical issues in different places of care, based on cancer diagnosis, physical and emotional symptoms based on life expectancy both for patient and professional dimensions, physical and emotional symptoms based on phase of illness, for professional dimensions, and physical symptoms from the patients’ viewpoint. Conclusions: The Portuguese IPOS is a reliable and valid measure.